Pengaruh Keragaman Produk, Kualitas Produk dan Promosi Terhadap Kepuasan Konsumen Pada Ramayana Panbil Kota Batam - Ratna Sari; Heryenzus (Komunitas Dosen Indonesia, 2023)
One of the most up-to-date retail complexes in Batam City is called Ramayana Panbil. Ramayana is able to fulfill the requirements of society because it satisfies customers' needs in terms of the range of products it offers, the quality of those products, and the promotions it runs. In addition, Ramayana has its own identity in the form of a label that markets products that are offered at low prices without sacrificing quality. Despite this, there are still issues that have not been completely handled, and these issues are connected to the product variety, product quality, and advertising. As a result, in the study that may be utilized as an objective where product variety, product quality, and marketing can effect customer happiness at Ramayana Panbil in Batam City, the phrase can affect consumer satisfaction was chosen. In the study that was carried out, it is possible to consult primary data sources and secondary data sources as references. Analytical tools are utilized in the process of conducting data analysis. These tools include data quality tests such as validity and reliability tests, classic assumption tests such as normality tests, multicollinearity tests, and heteroscedasticity tests, influence tests such as multiple linear regression analysis and coefficient analysis determination (R2), and hypothesis testing such as t test and f test. According to the findings of the research, there is evidence to suggest that Ramayana Panbil Batam City's product variety, product quality, and advertising all have the potential to have a positive and substantial impact on the level of satisfaction experienced by customers